The glorious flight across the Channel with Louis Bleriot, July 25, 1909 - Provensen, Alice; Provensen, Martin (New York, N.Y. Puffin Books, 1987)
A biography of the man whose fascination with flying machines produced the Bleriot XI, which in 1909 became the first heavier-than-air machine to fly the English Channel.
Reprint. Originally published: New York : Viking Press, 1983.
Keywords: Bleriot, Louis -- 1872-1936 -- Juvenile literature; Air pilots; Airplanes -- Design and construction